Socio-economic Transformation and Agrarian Adaptation: Mahaweli System H, Sri Lanka - M., Dharmasiri, L.; P, Jayathilake; Nishanthi, Karunaraj; K, Danasekara D.R.A.; C, Kanchana, R.A.; S, Ranwella, K.B.I.; G, Amarasinghe, A.; S, Rathnasekara (Indonesian Journal of Geography, 2025)
The global agricultural transition has created class divisions between the wealthy bourgeoisie and the laboring proletariat, thereby strengthening capitalist structures. Sri Lanka reflects this shift as it moves from subsistence to market-driven farming through policy and technological changes. The Mahaweli System H Area shows this transformation in land ownership, income, and livelihoods. Through a comprehensive investigation into the socio-economic changes in System H, this study examines the adaptive strategies employed by settlers to navigate these shifts. The mixed-method approach using the Convergent Parallel Design was applied, including semi-structured questionnaire survey and field observations. The survey was conducted with 40 settlers selected using a stratified random sample, with the consultation of the Mahaweli Residential Project Manager’s Office. The sample size was determined using a Standard Proportion-based formula with an 80% confidence level and 10% margin of error. The research identified four income categories: Higher Income (HI), Medium Lower Income (MLI), Lower Higher Income (LHI), and Lower Income (LI), illustrating the bourgeoisie and proletariat classes. Dynamic settlers expose adaptability and innovation, while conventional settlers maintain traditional practices, highlighting a socio-economic landscape. The study highlights the ongoing struggle of marginalized settlers and the complex interplay among socio-economic structures, government interventions, and individual resilience. While socio-economic dynamics persist within the framework of the bourgeoisie and proletariat, immediate radical transformations appear unlikely. The findings shed light on the difficulties of agrarian societies and offer insights into addressing vicious poverty in agrarian communities.